Designed Right...It Sells on Sight! - Hercules Incorporated (1949 Hercules Advertisements, 1949)
Color print advertisement for cellulosic plastics made with plastic molding compounds manufactured and sold by Hercules Powder Company. The advertisement features a photograph of a young boy using a plastic crossbow toy shaped like an airplane, identified as the K-Jet shooting toy. The accompanying text promotes the use of plastic in toy manufacturing. This advertisement appeared in Modern Plastics. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Hercules Incorporated; Corporations; Naval stores; Advertising, Industrial; Plastics; Plastics industry and trade; Plastic toys; Children in advertising; Cellulose; Cellulose industry; Cellulose acetate